“The Influence of Work Flexibility on Personal Interest in the Gig Economy Moderated by Self-Efficacy: An Islamic Work Ethics Perspective (Study on the Community in Subang Regency)”: “The Influence of Work Flexibility on Personal Interest in the Gig Economy Moderated by Self-Efficacy: An Islamic Work Ethics Perspective (Study on the Community in Subang Regency)” - Tigin Lugiani; Nunik Nurmalasari; Rd.Syeiren Christalia Nata Rahmat (STIESA Press, 2026)
The development of digital technology has led to the emergence of the gig economy, a flexible, project-based work system that is popular among young people. Flexibility in terms of time and location is the main attraction in choosing a job in this sector. However, not all individuals have the same interest in this work model, so it is necessary to understand the factors that influence this interest, one of which is work flexibility and self-efficacy. This study employs a quantitative approach using a survey method targeting 100 respondents in Subang Regency, selected through purposive sampling. The research instrument consists of a questionnaire analyzed using simple regression tests and Moderated Regression Analysis (MRA) to determine the relationships between variables. The results indicate that work flexibility has a significant positive influence on an individual's interest in the gig economy. Self-efficacy also has a positive influence on this interest. However, self-efficacy was not found to significantly moderate the relationship between work flexibility and interest in the gig economy (p = 0.332 > 0.05). This finding confirms that both variables are independent factors contributing to the choice to work in the gig sector